Diseño e implementación de un Sistema de Informacion Gerencial para Nefrocontrol S.A. - Rivera Rivera, Nela Melania (2015)
The importance of the implementation of a Management Information System in NEFROCONTROL S.A. lies in its ability to meet its performance on an ongoing basis, determining the critical issues affecting the management and prevent meeting the objectives. The lifting of information and validation of existing processes as well as other necessary proposals, help ensure the success, establishing mechanisms to keep the system updated. The Management Information System is designed in a technological platform called MySQL which has allowed the design in a friendly environment for the users, its design has been made considering the current needs and prospects easy future, all this considering the current resources of the company and the safety measures The development and implementation enables managers to be supported by accurate information to avoid making mistakes that affect the performance of the company or in turn lessen the impact thereof, so that it can gather data debug and transform them into information that provides knowledge to establish actions they deem necessary to achieve the stated goals KEYWORDS: capacity, performance, critical aspects, objectives, development, implementation, reporting, corrective actions, success.